Biofabrication of spatially organised tissues by directing the growth of cellular spheroids within 3D printed polymeric microchambers - Kelly, Daniel; Daly, Andrew C. (My University, 2019)
Successful tissue engineering requires the generation of human scale implants that mimic the structure, composition and mechanical properties of native tissues. Here, we report a novel biofabrication strategy that enables the engineering of structurally organised tissues by guiding the growth of cellular spheroids within arrays of 3D printed polymeric microchambers. With the goal of engineering stratified articular cartilage, inkjet bioprinting was used to deposit defined numbers of mesenchymal stem cells (MSCs) and chondrocytes into pre-printed microchambers. These jetted cell suspensions rapidly underwent condensation within the hydrophobic microchambers, leading to the formation of organised arrays of cellular spheroids. The microchambers were also designed to provide boundary conditions to these spheroids, guiding their growth and eventual fusion, leading to the development of stratified cartilage tissue with a depth-dependant collagen fiber architecture that mimicked the structure of native articular cartilage. Furthermore, the composition and biomechanical properties of the bioprinted cartilage was also comparable to the native tissue. Using multi-tool biofabrication, we were also able to engineer anatomically accurate, human scale, osteochondral templates by printing this microchamber system on top of a hypertrophic cartilage region designed to support endochondral bone formation and then maintaining the entire construct in long-term bioreactor culture to enhance tissue development. This bioprinting strategy provides a versatile and scalable approach to engineer structurally organised cartilage tissues for joint resurfacing applications.
PUBLISHED
Keywords: 3D-bioprinting; Stratified cartilage; Spheroid; Self-assembly; Osteochondral